Effects of self-management program on glycemic control in patients with type 2 diabetes and glycosylated hemoglobin - Shafigheh Pourverdi; Farahnaz Mohammadi Shahboulaghi; Zahra Kashaninia; Pourya Rezasoltani (Guilan University of Medical Sciences, 2015)
Abstract چمقدمه : نحوه ارتباط والدین با فرزندان با سبک فرزندپروری آنان ارتباط دارد.سبکهای فرزندپروری نقش مهمی در شکل گیری شخصیت بهنجار و نابهنجار در کودکان داشته و در صورت بکار گیری سبکهای ناکارآمد در تربیت کودکان می تواند منجر به پیامدهای منفی متعددی از جمله مشکلات رفتاری در آنان گردد.Introduction: Coronary artery bypass grafting surgery is a common therapeutic intervention in patients with coronary artery disease. This surgery has various complications. Electrolyte disorders are among common important complications among these patients. Objective: purpose of this study was to determine the level of electrolyte disorders and related factors in patients after coronary artery bypass grafting surgery hospitalized in cardiac care units. Methods: In this descriptive cross–sectional study, 288 Coronary Artery By Pass Graft (CABG) patients admitted to educational hospital were selected by gradual sampling. Data were collected by a three part researcher made questionnaire covering demographics, past medical history and levels of sodium and potassium through patients medical records. Statistical analyses were performed using appropriate tests (chi square test, fisher exact test and logistic regression). Rیافته ها: نتایج نشان داد که سبک فرزندپروری مقتدرانه هم با نمره کل مشکلات رفتاری درونی سازی (003/RResults: Findings showed that 16.7% of patients undergoing coronary artery bypass grafting were hyponatremia, 4.9% hypernatremia, 14.2% hypokalemia and 3.8% hyperkalemia. The results also indicated that there was a significant relationship between the factors such as body mass index, history of drug use, the number of vessels involved, the number of grafts, the length of time connected to mechanical ventilation, duration of artificial heart-lung machine use, aortic clamping time, and amount of intraoperative hypothermia, hemoglobin and hematocrit and postoperative electrolyte disorders (P<0.05). According to Logestic regression model, these factors were not associated to electrolyte abnormalities. Conclusion: The findings showed that many factors such as individual medical history and condition during surgery can affect electrolyte abnormalities after coronary artery bypass graft. Identifying these factors can be useful in planning for prevention, diagnosis and early treatment of possible complications which in turn may result in promotion of quality care.